METODE TAFSIR AL-WADHI A-MUYASSSAR KARYA M. ALI AL-SHABUNI - Ali Aljufri (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2016)
As a discipline, interpretation is inseparable from the method, which is a systematic way to achieve the level of a true understanding of the messages contained in the Qur'an. The introduction of the methodology in interpreting of the Qur'an is important to open our eyes to not only read commentaries that already exist, but also can see the new methodologies used by experts in contemporary interpretation. Methodology of contemporary modern interpretation is the study around the methods of interpretation that developed in the contemporary era. One method used by scholars of interpretation in the present era is to combine the interpretation of the history (bi al-ma'tsur) and using the ratio (bi al-Ra'yi) using a style that is easily understood.